PENGARUH PEMBERIAN EFFLUENTTERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (ElaeisguineensisJacq) DI MAIN NURSERY - Ira ' Yuliati; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Research aims to understand the influence of effluent and get doses good for growth seeds palm oil (elaeisguneensisjacq) in play a nursery. This study was conducted in the garden experiment the faculty agricultural university riau,campus binawidya km 12.5 simpang new, kecamatan handsome, pekanbaru,  with the height of 10 m dpl. This study was conducted for 4 months from of the months january until april 2016 .This report is written with design random complete ( ral ) non factor by treatment effluent doses consisting of 5 treatment that is E0 = 0 kg per plants, E1 = 1.5 kg per plants,E2 = 2 kg per plants, E3 = 2.5 kg per plants, E4 = 3 kg per plants.Of the treatment, each repeated three times, so as to produce 15 a unit of experiment. Each unit experiment consisting of 2 seeds,  it takes 30 seeds and 2 seeds plant of each unit experiment are only sampled with in averaged. Observed data analyzed by an analysis of variety and were then followed by test the distance worship of idols duncan’swhile 's 5 percent. The parameters that observed between increasing number of other high, the addition of another number of leaves, the increase in circumference stems and the addition of another broad leaves. The results of the study showed that the provision of effluent had have real impact on the addition of another tall plant, the addition of another number of leaves and the addition of another broad leaves, as well as not had have real impact on the increase in circumference the stem. The provision of effluent with a dose of 2.5 kg per plants exhibiting the growth of oil palm seeds good.   Keywords :  seeds palm oil, effluent,  waste